Total Synthesis of Aculeatins A, B and D and 6-epi-Aculeatin D via an Asymmetric Aldol Approach - Maram, Lingaiah; Das, Biswanath (Synthesis, 2014)
Simple and efficient stereoselective total syntheses of aculeatins A, B and D and 6-epi-aculeatin D starting from 1-tetradecanal have been accomplished. The synthesis is based on the Crimmins aldol reaction involving a chiral auxiliary.
Keywords: aculeatins; stereoselective total synthesis; Crimmins aldol reaction; chiral auxiliary; spirocyclization